Effects of Individual Differences on the Efficacy of Different Distracters During Visual Sexual Stimulation in Women. - Roberts, Verena; Prause, Nicole (Archives of Sexual Behavior, 2012)
Distractions from sexual cues have been shown to decrease the sexual response, but it is unclear how distracters decrease sexual response. Individual differences may modulate the efficacy of distracters. Forty women viewed three sexual films while their labial temperature and continuous self-reported sexual arousal were monitored. One sexual film had simultaneous verbal distracters concerning dissatisfaction with one's physical appearance (higher salience distracter), a second had distracters concerning daily chores (lower salience distracter), and the third sexual film had no distracters. Participant's reporting greater relationship satisfaction and more communication with their partner about their own physical appearance were expected to decrease the efficacy (increased sexual arousal) of the distracters concerning physical appearance. Contrary to expectations, women who received less feedback about their body from their partners reported less sexual arousal during a sexual film with body distracters than a sexual film with general distracters or a sexual film with no distracters. All women exhibited lower labial temperature in Minutes 2 and 3 of the sexual film with body image distracters as compared to the other two sexual films. Possible explanations explored include self-verification theory and individual differences in the indicators that women consider when rating their sexual arousal.